Internal Factor Corelation With Competence Test Grade Of Nursing Students Achmad Yani Yogyakarta - Deby Zulkarnain Rahadian Syah; Rahayu Iskandar (Alma Ata University Press, 2019)
The Constitution on National Education System No. 20 of 2003 Chapter II Article 3 states not only result and produce of smart human beings, but also has a solid and independent personality, as well as community and national responsibilities. A nurse's competence is something that a nurse carries out in providing professional services to the client, includes of knowledge, skills, and considerations required in practice situations. The purpose of research to determine the relationship of internal factors with the graduation of competency test of nursing students Stikes General Achmad Yani Yogyakarta. This research is a descriptive research, the scope of research Nursing Profession. This research was conducted at Stikes General Achmad Yani Yogyakarta. The data was taken with cross sectional approach and was correlational research. 30 respondents were taken with simple random sampling technique. The result of Gamma statistic test shows the value of p-value 0,617 which there is no relation between spiritual level with the graduation of competency test. Gamma statistical test results show the value of p value of 0.846 which means there is no relationship between the type of personality with the graduation of competency test. The result of Gamma statistic test shows the value of p value 0.143 which there is no correlation between level of anxiety with graduation of competency test. Conclusion teh research there is no relation between internal factor of spiritual level, personality type and anxiety toward passing competency test at Stikes General Achmad Yani Yogyakarta.